Structural equation modeling with Mplus : basic concepts, applications, and programming - Byrne, Barbara M. (New York : Routledge Academic, 2011)
'This text aims to provide readers with a nonmathematical introduction to the basic concepts associated with structural equation modeling, and to illustrate its basic applications using the Mplus program'--
Keywords: Mplus; Structural equation modeling -- Data processing; Multivariate analysis -- Data processing; Social sciences -- Statistical methods -- Data processing; PSYCHOLOGY / Statistics; EDUCATION / Statistics; SOCIAL SCIENCE / Statistics